OP07 What Shapes Participation in a Community-Based Intervention? Evidence from a Qualitative Evaluation of the Well London Project. (17th September 2012) - Jain, S; Draper, A; Clow, A; Lynch, R; Derges, J
Abstract : Background: This paper examines how individual and area-level contextual factors shape participation in a community-based development and health promotion intervention. Well London was a 3-year community development and health promotion programme for improving health behaviours (physical activity and healthy eating) and mental health and wellbeing in areas of high deprivation. The programme aimed to improve individual level health outcomes through a combination of neighbourhood and individual level interventions. Community engagement/participation was a central strategy of these interventions. Methods: A quantitative cluster randomised trial (CRT) was used to evaluate Well London in 20 neighbourhoods defined as Census Lower Super Output Areas (LSOAs). A qualitative study was nested within the trial to examine mechanisms and complexity. This study employed critical case sampling to select three intervention LSOAs that reflected a range of pre-existing community engagement and activities. In-depth semi-structured interviews were conducted with 59 respondents purposively sampled from each of 3 distinct areas. Each area reflected differences in implementation, nature of community life, and pre-existing community activities. Interviews addressed three topics: experiences of area, individual health & well-being, and knowledge of and involvement in Well London . Transcripts were coded and thematic analysis undertaken using NVIVO software. Results: Analysis found that area level and individual-level characteristics interacted to shape specific models of individual participation in each area. In an area with a 'dispersed' community, limited pre-existing activities and implementation through formal institutions, participation was attributed by respondents to self-motivation and responses to deprivation. In contrast, in the 2nd area, Well London implementation centred on an individual community organizer operating in a geographically close-knit area. Strong community interest and participation was shaped by the ability of this individual to inspire a sense of change. Finally, in an area with a 'saturation' of pre-existing activities, participation in Well London was part of a socially accepted pattern of community involvement. For new people to the area, involvement was viewed as aiding integration while for long-standing residents this was seen as a strategy to contribute to community life. Conclusion: Recent reviews on community participation present evidence of a causal link between participation and positive health outcomes. However, the mechanisms underlying this are not clear. The reasons people participate in Well London are shaped by interactions between individual and area-level factors. This suggests that understanding the link between community participation and health outcomes requires a contextualized analysis of why people participate and the meanings they associate with this.